PUPUK ORGANIK CAIR DARI LIMBAH PERTANIAN DAPAT MENINGKATKAN PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI EDAMAME - Sri Wahyuni; Indratin (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
Edamame soybean is highly nutritious and good for health. People started consuming soy a long time ago and it has high economic value. In crop cultivation, fertilizers are surely needed as plant nutrition. The difficulty in getting fertilizers can be solved by using agricultural wastes that are around us to be used as fertilizer solutions for plants. One way to increase soybean production is by utilizing liquid organic fertilizer (LOF). LOF can be used to increase soybean production. This organic fertilizer is a solution to replace the function of legumes in nutrient intake. The study used a completely randomized design (CRD) with 3 treatments; 1) LOF A (cow urine, sludge, husk ash, water, banana bunch, microbes); 2) LOF B (cow urine, sludge, husk ash, water); 3) LOF market and repeated 6 times. This study aims to obtain detailed information on the growth and increased in soybeans production by utilizing liquid organic fertilizer. Plants are sprayed evenly on the surface of the leaves every 1 week. The research was carried out in the Jakenan Experimental Garden Greenhouse from July - September 2020. The plant is used as edamame beans. The basic fertilizer used organic cow manure as much as 5 tons ha-1 which its application is used to cover soybean seeds when planting. The results showed that the use of liquid organic fertilizer enriched with microbes increased plant height, pod number, stover weight, and pod weight. Liquid organic fertilizer is one of the fertilization solutions for soybeans/beans.